Chemogenetic detection and quantitation of H2O2 in living cells - Eid, Mohammad; Barayeu, Uladzimir; Dick, Tobias P. (Nature protocols, 2025)
Hydrogen peroxide (H2O2) is a natural product of aerobic metabolism. It acts as a signaling molecule and regulates fundamental cellular functions. However, it has remained difficult to measure intracellular H2O2 with high specificity and in a quantitative manner. Here, we present a detailed protocol for a chemogenetic method that enables the detection and quantitation of H2O2 in living cells by converting intracellular H2O2 into fluorescent or luminescent signals. This is achieved by expressing the engineered heme peroxidase APEX2 in cells and subcellular locations of interest and by providing an appropriate fluorogenic or luminogenic substrate from outside. This method differs fundamentally from previously developed genetically encoded H2O2 probes; those are reversible and measure the balance between probe thiol oxidation and reduction. By contrast, APEX2 turns over its substrate irreversibly and therefore directly measures endogenous H2O2 availability. Our detailed step-by-step protocol covers the generation of APEX2-expressing cell lines, the implementation of fluorescent and luminescent measurements and examples for application. Ectopic expression of APEX2 can be achieved in 3 days, while the actual measurements typically require 1-2 h. This protocol is intended for entry-level scientists.
Im Text ist "2" jeweils tiefgestellt
Gesehen am 18.12.2025